COMPARISON OF STATIC BALANCE IN MALE FOOTBALL AND BASKETBALL PLAYERS BY USING FLAMINGO BALANCE TEST (International Journal of Physiotherapy, 2018)
Background: Balance plays a vital role in many sports. Static Balance has an exceptional effect on the performance of sports players and for injury prevention. Football and Basketball players require static balance for execution of sports specific skill. Thus, the purpose of this study was to compare the static balance in male football and basketball players.Methods: A total of 50 healthy male players, football (n=25) and basketball (n=25) from Sports Academies of Ahmedabad, Gujarat were selected for the study with purposive sampling. Static balance was assessed by using Flamingo Balance test.Results: Mann-Whitney Test was used to determine the significant difference between football and basketball players. The result of the study showed that there was a significant difference in static balance between male football and Basketball players(p